Overcoming Barriers for Indonesia’s Women-Led Food SMEs in Export - Wibowo, Wahyudi; Kristyanto, Visi Saujaningati; Sutedjo, Purnomohadi (International Journal of Entrepreneurship and Sustainability Studies, 2025)
This study examines the export potential of women-led Small and Medium Enterprises (SMEs) in Indonesia's processed food sector by identifying key challenges and proposing targeted strategies for growth. Using a mixed-methods approach, the research surveyed 191 SMEs and collected qualitative insights through Focus Group Discussions and in-depth interviews with women entrepreneurs. An analytical framework was employed to classify their export readiness. The findings confirm that while these SMEs possess significant export potential, they are constrained by interconnected barriers, including limited access to finance, insufficient knowledge of international markets, low digital literacy, and socio-cultural obstacles. A key contribution of the study is the classification of SMEs into three tiers of export readiness: "having export potential," "on the right track," and "not ready to export." This framework reveals the need for tailored support mechanisms rather than generic, one-size-fits-all solutions. The paper addresses a notable gap in research on the internationalization of women-led SMEs within a major developing economy. By applying a unique analytical framework to empirical data, it moves beyond a general discussion of barriers by offering specific and actionable policy recommendations tailored to the needs of women entrepreneurs in a sector critical for their economic empowerment.